2020
DOI: 10.1093/nutrit/nuaa005
|View full text |Cite
|
Sign up to set email alerts
|

The role of nutrition in asthma prevention and treatment

Abstract: Asthma is a chronic respiratory condition characterized by airway inflammation and hyperreactivity. Prevalence has continued to rise in recent decades as Western dietary patterns have become more pervasive. Evidence suggests that diets emphasizing the consumption of plant-based foods might protect against asthma development and improve asthma symptoms through their effects on systemic inflammation, oxidation, and microbial composition. Additionally, increased fruit and vegetable intake, reduced animal product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 144 publications
(174 reference statements)
5
104
0
2
Order By: Relevance
“…35 Children from less advantaged populations may also be impacted by disruptions to provision of school lunch programmes, with some evidence linking nutrition to respiratory outcomes in PWA. 36 How should PWA be managed when presenting with COVID-19? Guidance has been issued to PWA who suspect they may have COVID-19.…”
Section: Are Pwa At Increased Risk Of Contracting Covid-19?mentioning
confidence: 99%
“…35 Children from less advantaged populations may also be impacted by disruptions to provision of school lunch programmes, with some evidence linking nutrition to respiratory outcomes in PWA. 36 How should PWA be managed when presenting with COVID-19? Guidance has been issued to PWA who suspect they may have COVID-19.…”
Section: Are Pwa At Increased Risk Of Contracting Covid-19?mentioning
confidence: 99%
“…The effects of individual nutrients on health have been widely studied in order to better understand the effects of isolated compounds on different diseases. However, nowadays, the study of specific dietary patterns and foods as complex matrices and their effect on health and disease prevention is gaining attention [24]. Regarding this, diets rich in vegetables are clearly related with valuable effects in preventing different diseases, whilst diets rich in calories, and overall when that energy is mainly provided by fat-rich foods, are strongly linked with chronic inflammatory processes, such as asthma, among others [25].…”
Section: Role Of Micronutrients and Macronutrientsmentioning
confidence: 99%
“…Carotenoids as diet-derived antioxidants have antioxidant effects and can lower ROS activities, thereby reducing airway in ammation and improving lung function in asthmatic patients. The previous studies have shown that β-carotene can scavenge the highly reactive free radical superoxide anions and donate an electron to reduce free radical molecules to prevent oxidative damage (8,26). In addition, lycopene has been shown to suppresses Th2 responses, reduce eosinophilic in ltrates in the lungs, and reduce ovalbumin-induced airway in ammation in an animal model of allergic asthma (27,28).…”
Section: Discussionmentioning
confidence: 99%